2020
DOI: 10.1002/ppul.25070
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric lung imaging features of COVID‐19: A systematic review and meta‐analysis

Abstract: Rationale Pediatric COVID‐19 studies have been mostly restricted to case reports and small case series, which have prevented the identification of specific pediatric lung disease patterns in COVID‐19. The overarching goal of this systematic review and meta‐analysis is to provide the first comprehensive summary of the findings of published studies thus far describing COVID‐19 lung imaging data in the pediatric population. Methods A systematic literature search of PubMed was performed to identify studies assessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 53 publications
4
57
0
1
Order By: Relevance
“…Furthermore, compared to acute COVID‐19, we found that the prevalence of neurological symptoms was higher in MIS‐C, with a lower prevalence of respiratory symptoms 30,37–39 . Interestingly, our study also showed that infiltrates or opacities were less frequent in MIS‐C, whereas these are common findings in acute COVID‐19 40–44 . These findings can be useful clues to the development of an accurate diagnosis and case definition of MIS‐C.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, compared to acute COVID‐19, we found that the prevalence of neurological symptoms was higher in MIS‐C, with a lower prevalence of respiratory symptoms 30,37–39 . Interestingly, our study also showed that infiltrates or opacities were less frequent in MIS‐C, whereas these are common findings in acute COVID‐19 40–44 . These findings can be useful clues to the development of an accurate diagnosis and case definition of MIS‐C.…”
Section: Discussionsupporting
confidence: 57%
“…Notably, 17 patients with left lobe pneumonia had much higher creatine kinase and CK‐MB levels than patients with nonleft lobe pneumonia. The present findings support the point of view that chest CT manifestations in children with COVID‐19 are potentially a useful marker for early identification and severity assessment 16 …”
Section: Discussionsupporting
confidence: 86%
“…5 & 6 and Extended Data Table 3). For example, children might be differentially affected by COVID-19, including their manifestations in lung imaging 60 .…”
Section: Impact On Patient Carementioning
confidence: 99%